Does State Levies Policy Support Minapolitan Program In Indonesia - Rosdiana, Haula (UI Scholars Hub, 2013)
There has been no research that particularly and comprehensively analyzes state levies policy on fishery sector in Indonesia, although this is very important. The minapolitan (fisheries cities) program will support food sovereignty, at the same time functions as economic growth center in the regions. High state levies will impede fishery sector productivity, however on the other side, there must be state protection to maintain environmental sustainability and prevent excessive exploitations of natural resources. The state must also keep fishery product ruling in its own country by protecting it from the invasion of fishery product imports. Therefore state levies must be put in a balance position between budgetair (source of state finance) and regulerend (tools to manage state policy in the economic and social field) functions. Another newness offered by this research is the development of ‘the cost of taxation’ concept into ‘the cost of state levies’ concept. The development is grounded by an analysis that Non-Tax State Revenue (PNBP) has similar characteristics with taxation. In addition, the various state levies eventually cause compliance costs, in the form of direct money cost, time cost as well as psychological cost.